The general form of a quadratic equation is given by:
y = ax² + bx + c
Use the given values on the table to obtain a system of equations.
for the point (-3 , 0.5):
0.5 = a(-3)² + b(-3) + c
0.5 = 9a - 3b + c (1)
for the point (-2 , 1):
1 = a(-2)² + b(-2) + c
1 = 4a - 2b + c (2)
for the point (0 , 5):
5 = a(0)² + b(0) + c
5 = c
replace c= 5 into the equation (1) and (2) and simplify like terms:
0.5 = 9a - 3b + 5
-4.5 = 9a - 3b (3)
1 = 4a - 2b + 5
-4 = 4a - 2b (4)
multiply the equation (3) by -2 and multiply the equation (4) by 3, then, sum the equations:
9 = -18a + 6b
-12 = 12a - 6b
-3 = -6a
from the previous equation, solve for a:
-3 = -6a
a = 1/2
Next, replace a=1/2 into the equation (4) and solve for b:
-4 = 4a - 2b
-4 = 4(1/2) - 2b
-4 = 2 - 2b
2b = 2 + 4
2b = 6
b = 3
Hence, the values of a, b and c are:
a = 1/2
b = 3
c = 5